Soil Tillage for Sustainable Nutrient Management (Soil Tillage in Agroecosystems, 2002)
Soil cultivation has a large impact on factors governing plant nutrient dynamics. From practical experience farmers have known for a long time that soil cultivation causes increased mineralization of organic matter. This is particularly obvious when plowing in short-term leys and even more so when plowing in long-term leys orpermanent grassland. The opposite process, accumulation of organic matter and hence nutrients, as a result of reduced or no tillage, has been studied intensively only since the second half of the 20century, in conjunction with studies on reduced tillage.